2023
DOI: 10.1111/fcp.12936
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy with tamoxifen in breast cancer: From molecular mechanisms to targeted therapy

Abstract: BackgroundTamoxifen (TAM) is often recommended as a first‐line treatment for estrogen receptor‐positive breast cancer (BC). However, TAM resistance continues to be a medical challenge for BC with hormone receptor positivity. The function of macro‐autophagy and autophagy has recently been identified to be altered in BC, which suggests a potential mechanism for TAM resistance. Autophagy is a cellular stress‐induced response to preserve cellular homeostasis. Also, therapy‐induced autophagy, which is typically cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 174 publications
0
1
0
Order By: Relevance
“…However, recent studies have shown that the mechanism for certain anti-cancer drugs is linked to the induction of autophagy in cancer cells [100,101]. Recent studies have indicated that autophagy may serve as a mechanism of drug resistance to tumors [102][103][104]. Specifically, autophagy in traditional cancer treatments provides cells with an alternative survival route that circumvents cell death, potentially leading to treatment resistance.…”
Section: Autophagymentioning
confidence: 99%
“…However, recent studies have shown that the mechanism for certain anti-cancer drugs is linked to the induction of autophagy in cancer cells [100,101]. Recent studies have indicated that autophagy may serve as a mechanism of drug resistance to tumors [102][103][104]. Specifically, autophagy in traditional cancer treatments provides cells with an alternative survival route that circumvents cell death, potentially leading to treatment resistance.…”
Section: Autophagymentioning
confidence: 99%
“…Numerous risk factors are responsible for BC, including menopause, endogenous hormones, and oral contraception. Moreover, environmental factors, lifestyle, and family history have been identified to be accounted for developing breast mass (Key et al, 2001; Zamanian, Golmohammadi, Alalak, et al, 2023; Zamanian, Golmohammadi, Nili‐Ahmadabadi, et al, 2023). In recent decades, advanced therapy approaches and early identification through mammography lead to better prognoses and higher health outcomes (Ahmad, 2019).…”
Section: Introductionmentioning
confidence: 99%